182k views
5 votes
Find g(3) show all steps
g(3) = 2x + 4

User Coup
by
4.7k points

2 Answers

3 votes

Answer:

g(3) = 10

Explanation:

g(3) = 2x + 4

g(3) = 2(3) + 4

g(3) = 6 + 4

g(3) = 10

User AridTag
by
4.8k points
3 votes

Answer:

g(3) = 10

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Explanation:

Step 1: Define

g(x) = 2x + 4

g(3) is x = 3

Step 2: Evaluate

  1. Substitute: g(3) = 2(3) + 4
  2. Multiply: g(3) = 6 + 4
  3. Add: g(3) = 10
User Brandon Molyneaux
by
4.9k points